2012
DOI: 10.1016/s1474-4422(12)70004-2
|View full text |Cite
|
Sign up to set email alerts
|

Untreated clinical course of cerebral cavernous malformations: a prospective, population-based cohort study

Abstract: SummaryBackgroundCerebral cavernous malformations (CCMs) are prone to bleeding but the risk of intracranial haemorrhage and focal neurological deficits, and the factors that might predict their occurrence, are unclear. We aimed to quantify these risks and investigate whether they are affected by sex and CCM location.MethodsWe undertook a population-based study using multiple overlapping sources of case ascertainment (including a Scotland-wide collaboration of neurologists, neurosurgeons, stroke physicians, rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
261
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(287 citation statements)
references
References 35 publications
25
261
0
1
Order By: Relevance
“…Lifetime risk of clinically overt hemorrhage is >30%. Clinical disease aggressiveness is portended by early age of onset [3,27], high lesion burden [3] and multiple clinical bleeds resulting in disability [4]. Acute disease aggressiveness is characterized by recent clinical hemorrhage, which predicts a higher likelihood of future bleeding [5][6][7].…”
Section: Rock Activity In Leukocytes and Plasma Crp Activity Are Not Comentioning
confidence: 99%
See 1 more Smart Citation
“…Lifetime risk of clinically overt hemorrhage is >30%. Clinical disease aggressiveness is portended by early age of onset [3,27], high lesion burden [3] and multiple clinical bleeds resulting in disability [4]. Acute disease aggressiveness is characterized by recent clinical hemorrhage, which predicts a higher likelihood of future bleeding [5][6][7].…”
Section: Rock Activity In Leukocytes and Plasma Crp Activity Are Not Comentioning
confidence: 99%
“…While the CCM3 genotype portends more aggressive disease, the clinical behavior of CCM cases, regardless of genotype, remains widely unpredictable [3]. Some patients remain asymptomatic, while others are disabled from recurrent bleeds and/or high lesion burden [4]. Early age of lesion onset, multiple hemorrhages and increased lesion burden have been correlated in various studies with chronic disease severity [5][6][7][8][9].…”
mentioning
confidence: 99%
“…1,2 A CCM lesion consists of clusters of hemorrhagic dilated anomalous vessels ('caverns') lined by endothelium with defective intercellular junctions, and devoid of mature vessel wall angioarchitecture. 3,4 Multifocal CCM lesions arise in familial cases with autosomal dominant mutations in CCM1 (KRIT1), CCM2, or CCM3 (PDCD10) genes.…”
Section: Introductionmentioning
confidence: 99%
“…6 Other authors identified prior hemorrhage as an important risk factor for subsequent hemorrhage by comparing hemorrhage rates of CCMs with and without prior hemorrhage. 1,2,5,[7][8][9] According to these studies, hemorrhage rates ranged from 0%-6% and 4.5%-60%, depending on whether prior hemorrhage was or was not present, respectively. 1,2,5,7-9 However, these articles have a lack of comparability because of differing hemorrhage definitions.…”
mentioning
confidence: 99%